STABILITY OF VITAMIN C UNDER INFLUENCE OF RUTIN ADDITION AS ANTIOXIDANT - Rachmawati, Winasih
Background: Beverage supplements containing high dose of vitamin C (L-ascorbic acid) are widely available in the market. However vitamin C is unstable and can be easily oxidized to form L-dehydroascorbic. This reaction will be influenced by contact with air, moisture and water, under exposure to light, and high temperature. Addition of water-soluble antioxidant is a common method to prevent this reaction in beverage products. Rutin is a water-soluble bioflavonoid compound containing phenol groups and hence reported to show good antioxidant activities. The aims of this research were to obtain analytical method for the determination of vitamin C in the presence of rutin and to obtain data whether the addition of rutin is able to prevent the degradation of vitamin C under standardized experimental conditions. For this purposes a High Performance Liquid Chromatographic (HPLC) method for the quantification of vitamin C will be applied. Method: Prior the stability test, due to possible interference from rutin, an analytical method development for the determination of vitamin C in the presence of rutin should be performed which includes system suitability test and method validation. An HPLC method using Phenomenex C18 column (3.90 x 150 mm, 10µm), UV detector at 254 nm and methanol –formic acid 0.05% (20 : 80) mobile phase by gradient elution at 1.2 mL min -1 of flow rate was applied. The stabilities of vitamin C in solutions under influence and no influence of rutin were tested at incubation temperatures of 50 and 70 o C up to 2 days for test substance dissolved in phosphate buffer pH 5.4, while for that dissolved in mineral-free water up to 16 days. Result: Under the optimal condition, the method gave linear calibration curve over the range of 5.06 - 13.15 µg/mL for vitamin C with a regression equation of y = 36161.72x –96094 and regression coefficient of r = 0.9992. The limit of detection and limit of quantification for vitamin C were 0.75 dan 1.83 µg/mL respectively. The intra-day relative standard deviation (RSD) of the method were 0.595, 0.211 and 0.349 % respectively and inter-day RSD was 0.43 %. The recovery for vitamin C in sample simulation was in a range of 98.29 - 103.92 %. Independent of incubation temperatures, the results of stability test revealed that the addition of rutin was failed to prevent the degradation of vitamin C dissolved in both mineral-free water and phosphate buffer pH 5.4. Only slight inhibition of vitamin C degradation was observed from the 0 to 240 th hours in the case of vitamin C dissolved in mineralfree water and incubated at both 50 and 70 o C. The rate of degradation reaction occurred at second order for vitamin C and first order for vitamin C with addition of rutin (10:1) Conclusion: The method is suitable for the simultaneous determination of vitamin C and rutin in mixture solution without prior separation. The overall results of stability test revealed that the addition of rutin was failed to prevent the degradation of vitamin C under these experimental conditions.